2015
DOI: 10.3390/computation3040687
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation of Shale Gas Adsorption and Diffusion in Clay Nanopores

Abstract: Abstract:The present work aims to study the adsorption behavior and dynamical properties of CH4 in clay slit pore with or without cation exchange structures at sizes of 1.0 nm-4.0 nm using grand canonical Monte Carlo (GCMC) and molecular dynamics (MD) methods. The adsorption isotherms of CH4 have been investigated by GCMC simulations at different temperatures and various pore sizes. In the montmorillonite (MMT) clays without a cation exchange structure, from the density profile, we find the molecules preferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 41 publications
(48 reference statements)
4
33
0
Order By: Relevance
“…A similar finding was reported in a simulation study where water was found to reduce methane adsorption in clay pores. 12…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…A similar finding was reported in a simulation study where water was found to reduce methane adsorption in clay pores. 12…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…In addition to experimental studies, molecular simulation is considered as an effective tool to gain microscopic insights into complex physical phenomena or processes in many research areas [20][21][22][23][24]. The adsorption behaviors in nanopores of shale reservoirs were investigated via molecular simulation by many researchers [25][26][27][28]. The effects of temperature, pressure, and pore size on the adsorption performance of pure methane and a CO 2 /CH 4 mixture in the slit pore of shale formations were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Using the GCMC method, Sun et al (2015) performed research on the methane adsorption behaviours of different types of clay minerals (montmorillonite, illite and kaolinite) and also studied the effects of different temperatures on the methane adsorption behaviours. Sui et al (2015) studied the microscopic structural properties and diffusion behaviours of methane in slit-like montmorillonite pores using the GCMC and MD methods. Xiong et al (2016) studied the microscopic adsorption mechanism of methane in slit-like montmorillonite pores using the GCMC method.…”
Section: Introductionmentioning
confidence: 99%